Crisis management in the light of contemporary international relations - Andrić, Sanela D; Milašinović, Srđan М (Napredak, 2023)
The world has been in constant turmoil since the end of the Second World War and is facing numerous crises, conflicts and emergency situations, both of natural origin and those caused by the human factor. The pandemic that hit us in 2019-2020 and the worsening of the Ukrainian crisis (the Ukrainian-Russian conflict) emphasized all the weaknesses of the crisis response system at the national and global levels, reminding us why crisis management and constant study of (potential) crises are necessary. In the paper, we will look at the COVID-19 pandemic and the worsening of the Ukrainian-Russian conflict, because in the last three years these events have changed the geopolitical scene and introduced the world into a health, economic, security and social crisis.
Keywords: conflict; crisis management; contemporary crises; management